Rheology and sensory properties of microencapsulated propolis-enriched stirred-type yogurt - Taşdemir, Yasemin; Gölge, Evren (Italian Journal of Food Science, 2023)
In this study, the rheological, sensory and syneristic properties of yogurt enriched with 0.5%, 1% and 2% microencapsulated propolis (MP) was investigated. The viscosity measurements of stir-type yoghurt were performed with Brookfield DV-II viscometer. Shear rate varying between 0.02 s-1 and 100 s-1 flow models was obtained for rising and descending curves with the Rheocalc v3.3 software. Three flow models—Power Law, Herschel–Bulkley, and Casson models—were evaluated. All samples used in this analysis showed non-Newtonian and pseudoplastic properties. During the 21-day storage period, the Power Law flow model was optimal.